Filipinos in Davao and the "Land Problem" of the 1930's - Dacudao, Patricia Irene (2008)
This paper presents a narrative of the events that surrounded the "Davao Land Problem" issue of the 1930s, and the reaction of the Davao settlers vis-à-vis the national government at the time. This reaction was triggered by alarms over the involvement of the Japanese in the abaca industry of Davao, which attracted national attention to this periphery as Manila-based politicians and newspapers started voicing out mostly negative opinions about this "land problems." Most of the criticisms were leveled at the anti-nationalist nature of the land-labor contracts entered into by the mostly Filipino landholders with the Japanese during an era when economic nationalism prevailed. It explains why the Filipino settlers reacted the way they did and address center-periphery relationships between the socio-economic realities of frontier life in Davao and the political realities in the national capital.